Impact of changes in land use in the flow of the Para River Basin, MG/Impacto de alteracoes no uso do solo na vazao da Bacia do Rio Para, MG - Rodrigues, Evandro L; Elmiro, Marcos A.T; Braga, Francisco de A; Jacobi, Claudia M; Rossi, Rafael D (Revista brasileira de engenharia agrícola e ambiental, 2015)
Plant cover plays an essential role in the maintenance and balance of the hydrological cycle, performing functions in the control of water availability, which guarantee flow permanence. The use of mathematical models is an alternative to represent the hydrological system and help in the understanding of phenomena involving the variables of the water cycle, in order to anticipate and predict impacts from potential changes in land use. In the present study, the hydrological model SWAT (Soil and Water Assessment Tool) was used to analyse the dynamics of flow and water flow in the Para River Basin, Minas Gerais, Brazil, aiming to evaluate the impact caused by changes in land use in water availability. The adjusted model was assessed by the coefficient of efficiency of Nash-Sutcliffe (between -0.057 to -0.059), indicating high correlation and coefficient of residual mass (0.757 to 0.793) and therefore a satisfactory fit. An increase of about 10% in the basin flow was estimated, as a function of changes in land use, when simulating the removal of the original 'Cerrado' vegetation and of the seasonal semideciduous forest for pasture implementation in 38% of the basin. Key words: 'Cerrado' seasonal semideciduous forest flow A cobertura vegetal exerce papel fundamental na manutencao e no equilibrio do ciclo hidrologico, desempenhando funcoes no controle da producao de agua que garantem a permanencia de vazoes. O uso de modelos matematicos e uma alternativa para representar o sistema hidrologico e auxiliar na compreensao dos fenomenos que envolvem as variaveis do ciclo da agua para antecipar impactos decorrentes de eventuais mudancas no uso da terra. Neste trabalho e utilizado o modelo hidrologico SWAT (Soil and Water Assessment Tool) para analisar a dinamica da vazao na bacia do Rio Para, em Minas Gerais, Brasil, com o objetivo de avaliar o impacto provocado pelas alteracoes de uso do solo na disponibilidade de agua da bacia do Rio Para. O ajuste do modelo foi avaliado pelo coeficiente de eficiencia de Nash-Sutcliffe (entre -0,057 a -0,059) indicando alta correlacao e coeficiente de massa residual (0,757 a 0,793) e, portanto, um ajuste satisfatorio. Estima-se que houve incremento de cerca de 10% na vazao da bacia em funcao das alteracoes no uso do solo, contemplando basicamente a supressao da vegetacao original de Cerrado e de Floresta Estacional Semidecidual para implantacao de pastagem em 38% do territorio da bacia. Palavras-chave: Cerrado floresta estacional semidecidual vazao